Ptereleotris carinata, a new species of hovering goby (Perciformes: Microdesmidae) from the tropical eastern Pacific - Bussing, William A. (Revista de Biología Tropical, 2001)
A new hovering goby or dartfish is described from material collected in Mexico, Costa Rica and Panama. It is the only species of the cosmopolitan genus Ptereleotris known from the eastern Pacific. It is distinguished from its Western Atlantic and Indo-Pacific congeners by its low fin-ray counts, prominent median keel on the ventral margin of the head, lanceolate caudal fin with dusky lower half and dusky blue or lavender body in adults.